Management of late‐onset portal vein complications in pediatric living‐donor liver transplantation. (16th December 2013) - Cho, Yong‐Pil; Kim, Kyung‐Mo; Ha, Tae‐Yong; Ko, Gi‐Young; Hwang, Jae‐Yeon; Park, Hojong; Chung, Young Soo; Yoon, Taein; Hwang, Shin; Jun, Heungman; Kwon, Tae‐Won; Lee, Sung‐Gyu
Abstract The purpose of this study was to evaluate retrospectively the results of PTA for late‐onset PV complications after pediatric LDLT and to assess whether a meso‐Rex shunt is a viable option for treating restenosis of the PV after PTA in selected cases. Seventy‐five children who underwent adult‐to‐child LDLT were included in this study, and there were six late‐onset PV complications (8.0%). The initial therapeutic approach was PTA, with or without stent: PTA with balloon dilation for three children, PTA with stent placement for one child, and failure to cannulate the occluded PV for two children. A meso‐Rex shunt was performed in the two children after failed PTA: One suffered complete obstruction of the main PV, and the other, restenosis with total thrombosis after PTA with stent. The PTA was a technical and clinical success in four with PV stenosis of the six patients (66.7%), and successful application of a meso‐Rex shunt in the other two children resulted in restoration of PV flow. In conclusion, PTA is a safe and effective procedure for treating late‐onset PV stenosis after pediatric LDLT. However, in growing pediatric recipients with restenosis of the PV after PTA or chronic PV thrombosis, a meso‐Rex shunt may be a better choice for late‐onset PV complications.